The role of tiktok live shopping streamer in repurchase decision and impulsive purchase behavior - Sanjaya, Mikael; Berlianto, Margaretha Pink (Institute of Computer Science (IOCS), 2024)
The COVID-19 pandemic in 2020 triggered changes in consumer behavior and business practices. In response to the market challenges brought about by the pandemic, entrepreneurs and consumers alike shifted to online platforms, utilizing e-commerce as a vital channel for marketing. This research aims to investigate the factors influencing repurchase intentions and impulsive purchase behavior among TikTok live shoppers, specifically focusing on product quality, live streaming experiences, and streaming scenarios. The study was conducted among TikTok users in Indonesia with a sample size of 255 participants, utilizing the SmartPLS method for data analysis. The results indicate that product quality, live streaming experiences, and streaming scenarios significantly influence the TikTok platform's repurchase intentions and impulsive purchase behavior. The implications of this research underscore the importance of considering these factors in designing marketing strategies and product development in the digital era, particularly on social media platforms like TikTok, to enhance user engagement and overall business success